Progression of vowel production in children with cochlear implant - Tomić, Diana; Mildner, Vesna (2008)
The aim of this study was to analyze the progression of vowel perception and production in children with cochlear implants. Two-syllable nonsense words differing only in the vowel were presented visually and auditorily. The children repeated the word after a model and pointed to the one presented on a computer screen that they thought corresponded to the auditory stimulus. The responses were grouped in four groups: correct - stimulus repeated and pointed correctly ; uncertain-1 - stimulus repeated incorrectly and pointed correctly, uncertain-2 - stimulus repeated correctly and pointed incorrectly, and incorrect - stimulus repeated and pointed incorrectly. The acoustic analysis included F1 and F2 and was done for three groups - correct, uncertain-1 and uncertain-2. The two uncertain groups were compared with each other and with the correct group in terms of F1 and F2 defined vowel space. In both uncertain groups the vowels that are positioned more closely to each other were confused more frequently than those at the end points ot the vowle space. Acoustic analysis ot the correct responses revealed a high correlation between perception and production.
Projekt MZOS
ENG